Biomodulation of Non-Specific Immune Response in the Tiger Shrimp Penaeus MonodonFabricus With spirulina Iccorporated Diet - Jadhav visal Shripatro (Department of Aquaculture, College of Fisheries, 2002)
Black tiger shrimp; Penaeus monodon is an important species cultured all over the world. However, disease outbreaks have caused senous economic losses in several countries. For successful farming of shrimps disease prevention is a prime necessity The present study was designed to assess the immunostimulating potential of Spirulina and to see its effect on growth as well as colour of P. monodon juveniles. In this study, juveniles of P. monodon were used for evaluating the effect of different levels of Spirulina on growth, food conversion ratio, food conversion efficiency, survival as well as prophylactic potency of Spirulina evaluated by proPhenoloxidase activity, antibacterial assay, haemagglutinin assay, phagocytosis and challenge study Effect of Spirulina on colour of shrimps was also studied. Five experimental diets designed as T I to T 5 were prepared by using clam meat, Spirulina, rice bran, cod liver oil and vitamin- mineral mix. The total protein content of all diets were kept near to 40% and Spirulina was incorporated at 0%, 10%, 20%, 30% and 40% in diets by replacing clam meat. Completely randomized design with five treatments each having four replications was used for analyzing the results. In each tank ten numbers of Penaeus monodon juveniles were kept. Feeding was done for a period of 35 days. The test animals fed with diet containing Spirulina up to 30% incorporation showed better growth, food conversion ratio and food conversion efficiency. But survival during experiment was not affected by the addition of Spirulina. Spirulina incorporated treatments showed higher phenoloxidase activity than control. Antibacterial activity was also observed in the treatments incorporated with Spirulina, while in control no antibacterial activity was observed. Result of agglutinin activity was not